2012
DOI: 10.1016/j.febslet.2012.11.024
|View full text |Cite
|
Sign up to set email alerts
|

δ‐catenin overexpression promotes angiogenic potential of CWR22Rv‐1 prostate cancer cells via HIF‐1α and VEGF

Abstract: a b s t r a c tThis study revealed that CWR22Rv-1 cells overexpressing d-catenin display bigger tumor formation and higher angiogenic potentials than their matched control cells in the CAM assay. In addition, dcatenin overexpression in CWR22Rv-1 cells results in increased hypoxia-inducible factor 1-alpha (HIF-1a) and vascular endothelial growth factor (VEGF) expression. Furthermore, d-catenin overexpression was found to enhance nuclear distribution of both b-catenin and HIF-1a in hypoxic condition, which is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…In our previously study, we found that δ-catenin induces E-cadherin processing and activates the δ-catenin signaling pathway in prostate cancer [23]. We also demonstrated that δ-catenin promotes angiogenesis through stabilizing HIF-1α to activate VEGF in the CWR22Rv-1 prostate cancer cell line [24]. These studies suggest the important role of δ-catenin in prostate cancer.…”
Section: Introductionmentioning
confidence: 79%
“…In our previously study, we found that δ-catenin induces E-cadherin processing and activates the δ-catenin signaling pathway in prostate cancer [23]. We also demonstrated that δ-catenin promotes angiogenesis through stabilizing HIF-1α to activate VEGF in the CWR22Rv-1 prostate cancer cell line [24]. These studies suggest the important role of δ-catenin in prostate cancer.…”
Section: Introductionmentioning
confidence: 79%
“…δ-Catenin has also been implicated in the cell-cell interaction and signaling transduction in cancers including prostate (Burger et al, 2002;Lu et al, 2005;Lu et al, 2009), lung (Dai et al, 2011;Li et al, 2012;Zhang et al, 2010;Zhang et al, 2013b), ovarian (Fang et al, 2012), brain and colorectal tumors (Zhang et al, 2013a). Our previously published data shows that δ-catenin promotes angiogenesis through the stabilization of HIF-1α, activating VEGF in the CWR22Rv-1 prostate cancer cell line (He et al, 2013). We have also demonstrated that δ-catenin promotes E-cadherin processing, resulting in the activation of β-catenin-mediated oncogenic signals (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…It is interesting to note that the mechanism of hypoxic regulation is realized usually through transcription factor HIF, but there are many different factors which control the level of this transcription factor in low oxygen conditions as well as in malignant tumors under normoxic conditions [25,[28][29][30][31][32][33][34]. Hypoxia-inducible mir-210, transglutaminase, deltacatenin, c-Myc as well as ATR (ataxia telangiectasia and Rad3 related protein), which is a member of the phosphoinositide 3-kinase-related kinases family, are among them.…”
Section: Resultsmentioning
confidence: 99%